2005
DOI: 10.1124/jpet.105.088005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Metallopeptidases and Kinin Receptors in Swine Oropharyngeal Tissues: Effects of Angiotensin I-Converting Enzyme Inhibition and Inflammation

Abstract: Angiotensin I-converting enzyme inhibitors (ACEi) cause both chronic and acute side effects, including rare but potentially life-threatening angioedema (AE). The main hypothesis to be tested in this study was that metallopeptidases and kinin receptors are present in oropharyngeal tissues and that their expression is modulated by ACEi and inflammation. Novel realtime polymerase chain reaction analysis was developed and allowed the relative quantification of tissue's gene expression for neprilysin, membrane-boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
11
2
Order By: Relevance
“…Furthermore, many published techniques claiming high-quality RNA isolation from FR tissue either relied only on expression of HKGs [2,3] and A 260 /A 280 ratios [34,35] or did not perform RNA quality assessment at all [8,10,36]. Here we show that contrary to previous results with FR tissue [4,[37][38][39], the modified Arcturus RNA extraction method was optimal for the extraction of high-quality RNA compared with the Ambion and Sigma methods for cervical biopsy sections (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, many published techniques claiming high-quality RNA isolation from FR tissue either relied only on expression of HKGs [2,3] and A 260 /A 280 ratios [34,35] or did not perform RNA quality assessment at all [8,10,36]. Here we show that contrary to previous results with FR tissue [4,[37][38][39], the modified Arcturus RNA extraction method was optimal for the extraction of high-quality RNA compared with the Ambion and Sigma methods for cervical biopsy sections (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…We have recently observed that pigs undergoing long-term treatment with the angiotensin I-converting enzyme inhibitor enalapril exhibit a generalized B 1 receptor up-regulation (mRNA in several organs and endothelial immunoreactivity in tissue sections). This protracted response occurred without changes in the white blood cell counts or increases in the phase reactant C-reactive protein (Moreau et al, 2005a). On the other hand, pharmacological inhibition did not support important roles for tyrosine or MAP kinases in the basal or stimulated expression of B 1 receptors in the present cellular model (data not shown), in contrast to other in vitro systems Phagoo et al, 2001).…”
Section: Discussioncontrasting
confidence: 53%
“…Indeed, B 1 R expression in IMR-90 embryonic fibroblasts has been shown to be acutely stimulated by agonists of either the B 1 or B 2 Rs, but via the release of autocrine inflammatory cytokines (Phagoo et al, 1999). The protein kinase C-dependent and cytokine-independent pathway for B 1 R autoregulation would be compatible with the absence of systemic inflammation in pigs chronically treated with an ACE inhibitor (Moreau et al, 2005a) and with the repressor effect of 18 a B 1 R receptor antagonist on B 1 R mRNA expression in tissues of rats treated with such a drug (Marin-Castano et al, 2002). The lack of effect of all other tested peptides potentially affected by ACE inhibition also does not support that a cross-talk between peptides affected by ACE and macrophages has a role in vascular B 1 R expression.…”
Section: Cytokine-independent Induction Of B 1 R Expression Under Acementioning
confidence: 63%
“…Notably, in the porcine model, there was no evidence of systemic inflammation (fever, leukocyte count alteration, acute phase protein release) parallel to B 1 R expression (Moreau et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation